2021
DOI: 10.1002/ijgo.13823
|View full text |Cite
|
Sign up to set email alerts
|

The golden hour for postpartum hemorrhage: Results from a prospective cohort study

Abstract: Postpartum hemorrhage (PPH) has been a leading cause of global maternal mortality over the last 25 years. 1,2 It affects mainly young women in low-and middle-income countries and its impact on maternal mortality has increased from 68% in 1990 to more than 80% in 2015. [1][2][3] PPH has also increased in high-income countries where there is a higher rate of medicalization contributing to the condition. [4][5][6] PPH is also associated with maternal near-miss cases, Intensive care unit (ICU) admission, and massi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
1
8
1
1
Order By: Relevance
“…[18][19][20][21][22] Only a few studies have investigated the predictive performance of SI as an early predictor of PPH in a general population of women vaginal delivery including non-PPH women. 16,27,39 Most of these studies reported AUROC values for postpartum SI to discriminate blood loss ≥1000 ml higher than our findings, 16,27 with AUROC values of 0.70 or higher, a range considered acceptable by most authors. 29 These studies present methodological limitations by considering the highest SI value during the postpartum period 16,27 and failing to exclude women who had already met the outcome criteria when SI was measured.…”
Section: Discussioncontrasting
confidence: 63%
See 4 more Smart Citations
“…[18][19][20][21][22] Only a few studies have investigated the predictive performance of SI as an early predictor of PPH in a general population of women vaginal delivery including non-PPH women. 16,27,39 Most of these studies reported AUROC values for postpartum SI to discriminate blood loss ≥1000 ml higher than our findings, 16,27 with AUROC values of 0.70 or higher, a range considered acceptable by most authors. 29 These studies present methodological limitations by considering the highest SI value during the postpartum period 16,27 and failing to exclude women who had already met the outcome criteria when SI was measured.…”
Section: Discussioncontrasting
confidence: 63%
“…A prospective cohort of 270 unselected women after vaginal delivery conducted in Brazil in 2015 found an AUROC, sensitivity and specificity of SI for discriminating QBL ≥1000 ml similar to ours. 39 Those authors considered the mean value of SI between 21-40 and 41-60 minutes after delivery, an approach to the SI measurement timing consistent with ours, without the methodological limitation associated with using the highest SI value. 39 SI measured shortly after delivery is a poor predictor of PPH (QBL ≥1000 ml or cPPH).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations